Habilidad combinatoria general y específica de líneas endogámicas de maíz tolerantes a bajo fósforo - Salazar Villareal, Fredy Antonio; Narro Leon, LA; Vallejo Cabrera, Franco Alirio (2008)
Twelve corn inbreeds contrasting in P use efficiency available at CIMMYT collection of CIAT, Colombia were studied. The inbreeds and their diallel crosses were evaluated under 2 P levels (4 and 15 ppm) using the alpha lattice design. The genetic design was performed according to Hallauer and Miranda (1986). Highly significant differences were found among parents (P), crosses (C) and P vs C in both environments (low and high P levels). At low P, crosses sum of squares (SS) accounted for 66% of genotype SS while at high P, P vs C accounted for 58% of genotype SS, meaning that heterosis was more important at high P. At low P, significant differences were found for tolerant (T) parents vs susceptible ones (S). Crosses among TxT, SxS and TxS parents were different, suggesting a polygenic inheritance for this trait. General (GCA) and specific combining ability (SCA) were highly significant at low and high P but SCA was 3 fold the GCA, meaning that no additive gene effects were more important for P use efficiency.